Duel of Love in the Loving Novels of Gabriel García Márquez - Longan Phillips, Shirley (2016)
Duel is a word in Spanish with three different definitions: duel in terms of a battle; duel as mourning in terms of facing the absence of a person; and, as a verb, it is conjugated with the meaning of pain. This article plays with the three meanings of this word in order to study two loving novels: Love in Times of Cholera and Of Love and Other Demons. Both novels are from author Gabriel García Márquez. The characters studied are Fermina Daza and Florentino Ariza in the first novel and Cayetano Delaura and Sierva María de Todos los Ángeles in the second one. These characters face love, in terms of a painful combat against society and themselves. Also, they suffer in their bodies the havoc of love because they get sick with cholera or rabies. And, finally, they live and cry the pain of love because they suffer the absence of the loved one.